(untitled) (Research, Society and Development, 2022)
The NOVA classification is not yet widely understood by the entire population and studies evaluating knowledge about the degree of food processing in university students are still scarce. In addition, it is unclear whether there is a difference in knowledge about the degree of food processing between academic areas in universities. Knowing that less knowledge can be a risk factor for risky eating habits, this study aims to assess the knowledge about food processing grade among university students. A cross-sectional study with 977 students. The questionnaire assessed knowledge about the degree of food processing (in natura, minimally processed, processed and ultra-processed). A linear regression analysis was used to demonstrate an association between overall knowledge about the degree of food processing and sociodemographic variables, academic areas and initial knowledge about the Brazilian food guide. The overall knowledge mean about the degree of food processing was 2.57 (1.37). The linear regression showed an association between age (p<0.001), having initial knowledge about the guide (p=0.01), being from the area of “Agrarian Sciences” (p<0.001) and “Biological and Health Sciences” (p<0.001) presenting the highest scores in overall knowledge. There was low overall knowledge about the degree of food processing among university students. Federal actions are needed to address this issue.